Demographic and socio-economic characteristics, household food security status and academic performance among primary school children in North Kinta, Perak, Malaysia - Ahmad, Nor Syaza Sofiah; Sulaiman, Norhasmah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: Good academic performance is important for children to ensure their personal well-being. This cross-sectional study investigated the associations between demographic and socio-economic characteristics, household food security status and academic performance among primary school children at North Kinta, Perak, Malaysia. Methods: Two national primary schools were selected randomly and all Standard 5 and 6 students were invited to participate in this study. Self-administered questionnaire on demographic and socio-economic characteristics and food security status was completed by parents. The results from last year examination were acquired from the teacher to evaluate students’ academic performance. Results: Overall, 140 respondents were involved, in which 51.4% were male. A majority of the household (80.7%) displayed food insecurity. Multiple logistic regression revealed that students from well-off households were more likely to have higher marks in English Language Comprehension (OR=8.28, 95%CI: 1.49, 45.91), Writing (OR=25.02, 95%CI: 2.36, 265.69) and Mathematics (OR=7.79, 95% CI: 1.44, 42.11). Female students showed high odds to pass English Language Comprehension (OR=3.47, 95% CI: 1.49, 8.16) and Writing (OR=4.16, 95%CI: 1.51, 11.45) compared to male students. Conclusion: This study unveiled that gender and low household income results in the low achievement in students’ academic. Therefore, for the upcoming intervention programmes should focusing more on helping students from poor households in order to enhance students’ academic performance.